The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/jhr-10-2019-0225
|View full text |Cite
|
Sign up to set email alerts
|

Addictive use of smartphone, depression and anxiety among female undergraduates in Nigeria: a cross-sectional study

Abstract: PurposeThis study examined the prevalence and relationship between addictive use of smartphones and symptoms of depression and anxiety among female undergraduates.Design/methodology/approachStandardized scales were used to measure the addictive use of smartphones, depression and anxiety among 398 female students (mean age 21.75 years, SD = 2.67) at two large higher institutions in southwest Nigeria and were opportunely sampled. Two hypotheses were tested using Spearman's rho and Mann–Whitney U tests.FindingsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
11
2
Order By: Relevance
“…It is not surprising that more participants in this study experienced depression since the COVID-19 lockdown was something that put emotional strain on many people. Likewise, a somewhat lower prevalence rate of depression -21.6% -was reported by Ayandele et al [36)] in 2019, among undergraduate students in five universities located in the same region where the present study took place.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…It is not surprising that more participants in this study experienced depression since the COVID-19 lockdown was something that put emotional strain on many people. Likewise, a somewhat lower prevalence rate of depression -21.6% -was reported by Ayandele et al [36)] in 2019, among undergraduate students in five universities located in the same region where the present study took place.…”
Section: Discussioncontrasting
confidence: 50%
“…While Cao et al [17) collected data in February 2020, before the pandemic reached its peak in most parts of the world, data collection for this study occurred in May 2020, a period during which the cases were increasing exponentially in Nigeria. Some authors, [36], had reported a lower rate of anxiety, 14.8%, before the COVD-19 pandemic, among undergraduate students in five universities in South-western Nigeria. Again, this is not surprising since several studies that took place in Italy, United States, China and Spain, [18–20, 32, 37], have averred that the lockdown/self-quarantine associated with the COVID-19 was putting a lot of psychological strain on college students…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of smartphone addiction in our study population was 54.2%: this is signi cantly higher than most global estimates [28,29]. Two similar studies on Nigerian (N=398) and Cameroonian (N=634) university students, using the Smartphone Addiction Scale-Short version, yielded prevalence rates of 18.4% [20] and 21.0 % [30], respectively. Nevertheless, our results are comparable to ndings from studies on university students from Saud Arabia (N=2367) [29] and Egypt (N=700) [31].…”
Section: Discussioncontrasting
confidence: 41%
“…The sample size was estimated using STATA, based on a prevalence of 18.4% from a Nigeria [20]. Six hundred participants were required at a 95% con dence interval and a 5% margin of error.…”
Section: Sampling and Sample Size Calculationmentioning
confidence: 99%
“…[28] A Nigerian study reported Cronbach's alpha 0.85 as the reliability coefficient for this scale. [29] For this study, comorbid depression and anxiety was determined when respondents scored above the cut-off score for depression (GDS-SF score ≥ 5) and anxiety (GAD ≥5). The respondents were divided into four groups: respondents with no anxiety and depression, respondents with comorbid depression and anxiety, respondents with anxiety only and respondents with depression only.…”
Section: Annals Of Health Research Volume 6 Issue No 4 2020__________...mentioning
confidence: 99%